Tax Amnesties : Theory, Trends, and Some Alternatives - Le Borgne, Eric (International Monetary Fund, 2008)
Tax amnesties remain as popular as ever as a tool for raising revenue and increasing tax compliance. International experience, however, shows that the costs of tax amnesty programs often exceed the programs' benefits. This paper weighs the advantages and disadvantages of tax amnesties, drawing on results from the theoretical literature, econometric evidence, and selected country and U.S. state case studies. The authors conclude that 'successful' tax amnesties are the exception rather than the norm. Improvements in tax administration are the essential ingredient in addressing the main problems that tax amnesties seek to address. Indeed, the most successful amnesty programs rely on improving the tax administration's enforcement capacity. ?Given the potential drawbacks of tax amnesties, a few alternative measures are discussed.